The The Effect of Contextual Problem-Based Leaning Model on Students’ Environmental Liteacy in Environmental Education Course (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The 21st century is characterized by transformation and advancement across multiple domains. These modifications encompass requirements within the educational sector. This essay seeks to analyze the opportunities and obstacles of environmental literacy and awareness in 21st-century schooling. This study sought to determine the impact of contextual problem-based learning on students' environmental literacy. The research employed a posttest-only approach and constituted a quasi-experimental study. The control group underwent conventional training, while the experimental group engaged in contextual problem-based learning. The environmental literacy of students was the dependent variable in this study. The independent variable in this study was contextual problem-based learning. Sixty pre-service biology educators from two complete courses participated in the research during their first semester. The assessments of recent environmental literacy competencies were utilized as study instruments. The research findings indicate a disparity in students' environmental literacy between those subjected to contextual problem-based learning and those who undergo traditional education. The experimental group exhibited superior environmental literacy compared to the control group. Consequently, contextual problem-based learning is a viable approach for augmenting students' environmental knowledge.